Tourism in Smart Specialisation in Regions of Eastern Poland - Zielińska-Szczepkowska, Joanna; Sawulska-Kamińska , Donata (Studia Oeconomica Posnaniensia, 2018)
The aim of the considerations assumed in the present paper is to analyze the smart specialization of five regions of Eastern Poland, with particular emphasis on trends in tourism specialization and its links with other sectors. The following research methods were used in the work: deductive studies of literature on the topic (national and foreign) as well as programme documents and legal acts for analyzed regions which were made in the years 2013 to 2015 and which are in force in the III programming period for the years 2014-2020. The concept of smart specialization is based on the theories of regional development and the methodologies used to select smart specialization by individual regions. The paper also includes a spatial analysis of smart specialization with regards to tourism. The carried out studies prove that tourism plays an important role in the socio-economic development of the regions of Eastern Poland as it has been selected for smart specialization (leading or supporting) in all of the analyzed regions.